2021
DOI: 10.1099/jgv.0.001657
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic landscape of Japanese encephalitis virus-infected fibroblasts

Abstract: Advances in proteomics have enabled a comprehensive understanding of host–pathogen interactions. Here we have characterized Japanese encephalitis virus (JEV) infection-driven changes in the mouse embryonic fibroblast (MEF) proteome. Through tandem mass tagging (TMT)-based mass spectrometry, we describe changes in 7.85 % of the identified proteome due to JEV infection. Pathway enrichment analysis showed that proteins involved in innate immune sensing, interferon responses and inflammation were the major upregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 64 publications
3
9
0
Order By: Relevance
“…Robust activation of GBPs in response to JEV infection at both the transcript and protein levels has been shown in our previous studies on human monocyte derived dendritic cells and mouse embryonic fibroblasts ( Chauhan et al., 2021 ; Sharma et al., 2021a ). Here, we found that GBP1 expression was markedly induced in human epithelial HeLa cells upon JEV infection, and interestingly GBP1 strongly colocalized with JEV-NS1 protein that marks the virus replication complex.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Robust activation of GBPs in response to JEV infection at both the transcript and protein levels has been shown in our previous studies on human monocyte derived dendritic cells and mouse embryonic fibroblasts ( Chauhan et al., 2021 ; Sharma et al., 2021a ). Here, we found that GBP1 expression was markedly induced in human epithelial HeLa cells upon JEV infection, and interestingly GBP1 strongly colocalized with JEV-NS1 protein that marks the virus replication complex.…”
Section: Discussionsupporting
confidence: 65%
“…A detailed understanding of the host-virus interaction is critical for the development of effective antivirals ( Turtle and Solomon, 2018 ; Sharma et al., 2021b ). While there are a few reports that have suggested the induction of various interferon-stimulated genes (ISGs) at both transcription and protein levels during JEV infection ( Yang et al., 2011 ; Zhang et al., 2013 ; Chauhan et al., 2021 ; Sharma et al., 2021a ), the finer details of the innate immune landscape during JEV infection remain largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…There have been a handful of studies utilizing ELISA methods to target specific proteins, however these rarely used power calculations in their experimental design, nor did they include adequate controls (48)(49)(50)(51)(52)(53). Analysis of the transcriptome and proteome in animal models (54)(55)(56)(57)(58) and cell culture (48,54,(59)(60)(61)(62)(63)(64) have been performed, however the comparability to human CSF and comparison with other neurological infections is limited. Furthermore, mRNA expression does not directly correlate with that of the corresponding protein (65).…”
Section: Discussionmentioning
confidence: 99%
“…Even though disrupting this interaction did not affect virus replication, it led to lower protein aggregates in mouse brain and reduced neurological symptoms. For JEV, Sharma et al (2021) have shown that autophagy acts as an antiviral response during JEV infection in neuronal cells. They also observed NS1 colocalization with LC3-I, an important autophagy protein whose depletion caused decreased viral titers.…”
Section: Flavivirus Interactions For Host Processes Outside the Ermentioning
confidence: 99%